Dilemmas of a Successful People's Education Movement in India. - Zachariah, Mathew (1989)
Government policies of developing nati.ons to stimulate economic development do not necessarily improve the living conditions of their citizens, most of whom are economically poor and politically powerless. A major criticism of attempts by most Western and national governments to promote development is that they serve only the elite. This study of the Kerala Sastra Sahitya Parishad (KSSP) discusses the limitations and potential of a popular education movement in India. The KSSP, which translates into "Kerala Science Literature Society," was begun in 1962 to make scientific knowledge available to the people in the language of the state. Growth in membership has been accompanied by an increasing involvement with left-wing political activists. Dilemmas facing the KSSP are conflicts between Marxist and middle-class leadership over definition of "the people" and "science" and the relationship of science to religion and to the state. Lessons that can be learned from the KSSP movement demonstrate: the importance of an independent, sufficient financial base; leadership dedication to original objectives; a large "critical mass" of volunteers; less organizational hierarchy; recruitment of the elite; alliance with other organizations; and utilization of the arts as information disseminators. Despite its problems, the KSSP provides an innovative, indigenous model for mass educational reform.